Five new species of Pleurothallis (Orchidaceae: Pleurothallidinae) in subsection Macrophyllae-Fasciculatae from Southeastern Ecuador - Jiménez, Marco M.; Vélez-Abarca, Leisberth; Mashendo-Jimbicti, Viviana; Garzón-Suárez, Henry X.; Monteros, Marco F.; Wilson, Mark (Phytotaxa, 2023)
Five new species of Pleurothallis subsect. Macrophyllae-Fasciculatae from Ecuador are described and illustrated: P. kashi-menkakarai, P. lapoi, P. marioandresavilae, P. sabanillae and P. tinajillensis. The taxonomic similarities of the new entities are discussed and information about their distribution, habitat, and conservation status is provided. Additionally, the first known and confirmed locality for Pleurothallis saueri is provided, a previously described species without collection data, as well as a lectotype is designated for this name.